1988
DOI: 10.1177/104225878801300104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consulting on Small Business: A Further Examination

Abstract: The present study focuses on the impact of consulting on small businesses and identifies the reasons why small businesses do not implement some of the recommendations that they receive from consultants. A mail survey of 126 businesses that had sought assistance from the SBDC at the University of Utah was conducted. Results obtained from 106 respondents (84% response rate) indicate that overall, business manager/owners were highly satisfied with the services they received and that they found them useful. They a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Chrisman and Katrishen (1995) found that the clients of the Small Business Development Center (SBDC) programme in the USA increased sales and employment significantly more than they would have done if no assistance had been received. Similarly Nahavandi and Chesteen (1988) reported that business managers were highly satisfied with the services received from a particular SBDC and that consulting had a positive impact on their business. Incubators for start-up businesses linked to universities are often mentioned as a measure that facilitates business development.…”
Section: Characteristics Of the Public Advisory Service Marketmentioning
confidence: 95%
“…Chrisman and Katrishen (1995) found that the clients of the Small Business Development Center (SBDC) programme in the USA increased sales and employment significantly more than they would have done if no assistance had been received. Similarly Nahavandi and Chesteen (1988) reported that business managers were highly satisfied with the services received from a particular SBDC and that consulting had a positive impact on their business. Incubators for start-up businesses linked to universities are often mentioned as a measure that facilitates business development.…”
Section: Characteristics Of the Public Advisory Service Marketmentioning
confidence: 95%
“…It provides free, comprehensive managerial planning assistance to owner-managers of new and small firms, as well as continuing education seminars and workshops, small business research, government procurement assistance, export services, and minority support programs. Several studies have indicated that the SBDC program contributes economic value to entrepreneurs (e.g., Chrisman, 1999;Chrisman et al, 1987;Chrisman and Katrishen, 1994;Chrisman and McMullan, 2000;Nahavandi and Chesteen, 1988;Pelham, 1985;Robinson, 1982).…”
Section: An Overview Of the Sbdc Programmentioning
confidence: 98%
“…Over the last 20 years, a considerable body of research has accumulated in the United States that suggests outsider assistance can have a substantial impact on new venture startup, survival, and performance (Chrisman and Katrishen 1994;Nahavandi and Chesteen 1988;Pelham 1985;Robinson 1982). For example, outsiders may assist entrepreneurs to develop an effective network (Hansen 1995), to build a management team (Rice 2002), to raise capital (Bygrave and Timmons 1992), and to prepare a business plan (Smeltzer, Van Hook, and Hutt 1991).…”
mentioning
confidence: 99%